Use Benchmarking to Help Manage Your Utility's Performance. Issue 6 (30th May 2019) - Haskins, Scott; Brueck, Terry
Abstract : Benchmarking offers key tools and industry‐developed processes for water utility management success. AWWA's Utility Benchmarking Program is a remarkable tool for improving efficiency, quality, and effectiveness.